Linguistic Mobility in the Central European Periphery and Multiethnic Heritage at the Beginning of the 20th Century - Oto Luthar (Dve Domovini, 2014)
By analyzing language use related to food, the author attempts to demonstrate that despite the allencompassing nationalist identity, the people living in Central European border areas in the late nineteenth and early twentieth century still shared in their everyday lives the same transnational rhetoric for both self-identification and recognition of others. Using a manuscript collection of recipes and other household instructions for housewives, where two and sometimes even three languages are used in a single paragraph, the author argues that this multicultural way of remembering and sharing professional expertise was the usual practice of everyday communication until the end of the Second World War, when the creation of socialist Yugoslavia led to the formation of three newly politicized nationalities/ ethnicities, two religious identities and (after 1945) one exclusive ideology that produced a new set of practices of cohabitation and differentiation.